3D printing bone scaffold based on TPMS structure as well as preparation method and application of 3D printing bone scaffold
Through 3D printed bone scaffolds based on TPMS structure, combined with moxifloxacin/rifampin PLGA microspheres and BMP-2, the problem of difficulty in reaching antibiotics in the treatment of infectious bone defects and slow bone regeneration speed is solved, and early antibacterial effects and later bone regeneration promotion are achieved.
Patent Information
- Application Number
- CN202411752147.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The prior art is difficult to effectively treat infectious bone defects, especially in the special structure and ischemia of the bone, making it difficult for antibiotics to reach the lesions, and the bone regeneration speed is slow and the vascularization effect is poor.
Ti-6Al-4V powder was prepared by selective laser melting method using 3D printed bone stents based on TPMS structure to form bone stents with good bionic characteristics and large specific surface area, and moxifloxacin/rifampin PLGA microspheres and BMP-2 were loaded inside it, fixed by hydrogel to form a spatiotemporal and sustained release timing control structure.
This bone stent has stronger antibacterial ability in the early stage, and can still promote rapid bone regeneration in the later stage, regulate the growth of osteoblasts and osteoclasts, significantly improving the therapeutic effect of infectious bone defects.
Smart Images

Figure CN119548670A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bone repair materials, and more specifically, particularly relates to a 3D printed bone scaffold based on a TPMS structure, and a preparation method and application thereof. Background Art
[0002] Infected bone defects are mainly caused by high-energy injuries and implants. Fractures caused by high-energy injuries are often Gustilo III type fractures, which are severely comminuted, with severe soft tissue damage and severe contamination. Severe contamination and tissue ischemia are the best conditions for bacterial growth and reproduction. About 5-30% of such injuries will eventually develop into chronic osteomyelitis and finally become infected bone defects. Implant surgery, including internal fixation and artificial joints, has a stable incidence of postoperative infection of 2-5% in recent years. If not handled properly, it will lead to infectious osteomyelitis and eventually develop into infected bone defects.
[0003] The pathogenic bacteria of infection of these two types of factors are mainly Staphylococcus aureus (S. aureus). The bone infection caused by S. aureus is a serious recurrent chronic inflammatory disease. The pathogenesis of S. aureus mainly includes three aspects. The first is that the bacteria adhere to the body to produce bacterial biofilm, which is used to protect the bacteria from antibiotics and the body's immune ability. Then the continuous reproduction causes a serious inflammatory response, and then the host will gradually develop bone ischemia necrosis, osteoclast autophagy and finally bone defects. The second is that bacterial infection of the bone is difficult to cure because the special structure of the bone and local ischemia make it difficult for intravenous administration to reach the lesion site. On the contrary, bacteria can easily attach to extracellular matrix proteins, evade the immune system and flexibly penetrate tissues. Third, the host's defense response to invading bacteria causes the host's defense cells to gather in the infected bones, making the local inflammatory response more severe. In this vicious cycle, the infection becomes more and more serious. Ultimately, bone infection and bone defects coexist.
[0004] The treatment of infected bone defects is a common problem that is difficult to solve in the medical industry around the world, which brings a huge economic burden to society and families. According to research reports, as of 2020, the cost of treating infected bone defects in the United States has exceeded 1.62 billion US dollars, of which the cost of treating each infected bone defect patient is as high as 150,000 US dollars. The high cost of treatment is mainly due to the long course of the disease and repeated surgeries. At present, the most commonly used treatment methods in clinical practice are bone grafting at the defect after controlling the infection, Masquelet technology and bone transport technology. The development of orthopedic device manufacturers in my country started in the 1980s. In recent years, the rapid development of additive manufacturing (3D printing) technology has brought revolutionary changes to the design and manufacture of orthopedic implants. It can be seen from the 3D printed orthopedic implant products that have been launched at home and abroad that the design concept of the product has not broken away from the constraints of traditional implants. In terms of functionality, the 3D printed porous titanium implant is simply used as a prosthesis, which only plays the role of defect filling, without giving it biological functions, and only achieves bone integration through passive bone growth. As a result, bone regeneration is slow, vascularization is poor, and bone ingrowth depth is limited.
[0005] Therefore, it is urgent to develop a new material for the treatment of infected bone defects. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a 3D printed bone scaffold based on TPMS structure, which has good biomimetic properties and a large specific surface area. In application, the two key points of early thorough debridement and high-concentration antibiotic treatment, and later guided bone rapid regeneration are grasped, and a 3D printed anti-infective bone scaffold based on TPMS structure is formed by carrying drugs. Suitable drugs are selected and the sustained release pathway of the drugs is determined. First, two targeted antibiotics are simultaneously loaded in polylactic acid-glycolic acid (PLGA) microspheres using a certain process, and the particle size of the microspheres is reduced to the optimal 5-10um, and the antibacterial ability of the double antibiotic-loaded microspheres is confirmed by in vitro antibacterial experiments. A titanium scaffold with a peripheral porosity of 90%, a central porosity of 55%, a diameter of 15mm, and a height of 2mm of the TPMS structure is prepared by a biological 3D printer, and then the PLGA microspheres and BMP-2 are loaded into the TPMS scaffold of the G unit structure by hydrogel, with BMP-2 in the inner layer and the PLGA microspheres in the outer layer, forming a spatiotemporal sustained release sequential regulation structure. The prepared bone scaffold has stronger antibacterial ability in the early stage, and mainly promotes osteogenesis in the later stage, but still maintains a certain antibacterial ability to regulate the growth of osteoblasts and osteoclasts. A preparation method and application of the bone scaffold are also provided.
[0007] The present invention provides a 3D printed bone scaffold based on a TPMS structure, characterized in that: the bone scaffold is prepared by 3D printing using Ti-6Al-4V powder as a building material, the bone scaffold is a G unit structure of TPMS, the porosity increases radially from the inner layer to the outer layer, the pore size range is 420 to 630 μm, the inner layer porosity is 55%, the peripheral porosity is 90%, the scaffold diameter is 15 mm, and the height is 2 mm.
[0008] A method for preparing a 3D printed bone scaffold based on a TPMS structure is also provided, which is characterized in that:
[0009] Using 3D printing technology, Ti-6Al-4V powder was used as the building material and prepared by selective laser melting (SLM);
[0010] The sample was constructed layer by layer with a 30 μm laser spot;
[0011] The printing laser power was 100 W, the hatch spacing was 70 μm, the laser scanning speed was 400 mm / s, the build plate temperature was 35 °C, and the alternating hatch mode was adopted as the scanning strategy.
[0012] Preferably, when constructing the sample layer by layer, each layer has a thickness of 50 μm;
[0013] The 3D printing process is carried out in an argon atmosphere;
[0014] After the SLM process, the samples were cleaned and cooled to room temperature.
[0015] Also provided is a 3D printed bone scaffold based on a TPMS structure prepared by the above-mentioned method for preparing a 3D printed bone scaffold based on a TPMS structure, characterized in that:
[0016] The bone scaffold is a G unit structure of TPMS, with porosity increasing radially from the inner layer to the outer layer, a pore size range of 420-630 μm, an inner layer porosity of 55%, a peripheral porosity of 90%, a scaffold diameter of 15 mm, and a height of 2 mm.
[0017] Based on the above-mentioned 3D printed bone scaffold based on the TPMS structure, a 3D printed anti-infection bone scaffold based on the TPMS structure is provided, characterized in that: moxifloxacin / rifampicin PLGA microspheres and BMP-2 are loaded inside the above-mentioned 3D printed bone scaffold based on the TPMS structure and fixed with hydrogel.
[0018] Preferably, when loading, moxifloxacin / rifampicin PLGA microspheres are prepared first, and the preparation is carried out by the double emulsion-solvent evaporation method, the external phase liquid is the oil phase, and the internal phase liquid is the water phase; the preparation method of the external phase liquid is as follows: liquid paraffin, petroleum ether and moxifloxacin are taken in a beaker, stirred to make them fully saturated, and then centrifuged to take the supernatant, 0.1% Span85 is dropped into the supernatant and stirred again, the liquid paraffin: petroleum ether: moxifloxacin = 5ml: 5ml: 2mg; the preparation method of the internal phase liquid is: take an appropriate amount of PLGA and dissolve it in acetonitrile and isopropanol solution, vortex, ultrasonic, then add moxifloxacin and rifampicin, continue to vortex and then add dichloromethane, vortex again to make it fully dissolved, the acetonitrile: isopropanol: PLGA: moxifloxacin: rifampicin: dichloromethane = 15ul: 75ul: 8mg: 1mg: 1mg: 10ul.
[0019] Preferably, after the external phase liquid and the internal phase liquid are prepared, first take an appropriate amount of the external phase liquid in a beaker for shearing and set aside, add the internal phase liquid to the external phase liquid, shear on a high-speed disperser, then add the external phase liquid, place it on a vortex machine and vortex it. As the vortexing proceeds, small pink particles of microspheres are seen in the solution, and then centrifuge to discard the supernatant, add detergent and vortex centrifuge to obtain microspheres, and fully dry them on a culture dish to obtain moxifloxacin / rifampicin PLGA microspheres; the external phase liquid added first: the internal liquid: the external phase liquid added later = 20ml: 1ml: 30ml, and the washing liquid is prepared by petroleum ether and n-hexane in a 1:1 ratio.
[0020] Preferably, the bone scaffold is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, sterilized by high-pressure steam sterilization, and then dried for use; the sterilized and dried scaffold is placed in a suitable flat-bottomed container, and the prepared moxifloxacin / rifampicin PLGA microspheres are fully mixed with the hydrogel, poured into the flat-bottomed container, so that the hydrogel fully wraps the scaffold, vortexed on a vortex oscillator, and irradiated with a 405nm ultraviolet flashlight to photocured the hydrogel to obtain a semi-processed scaffold;
[0021] After waiting for 24 hours, the BMP-2 solution was dissolved in the hydrogel, and then the BMP-2-containing hydrogel was poured into the semi-processed scaffold made on the first day, vortexed on a vortex oscillator, and irradiated with a 405nm ultraviolet flashlight to photocured the hydrogel to obtain a 3D printed anti-infection bone scaffold based on the TPMS structure.
[0022] Also provided is the use of the above-mentioned TPMS-structure-based 3D printed bone scaffold and / or the TPMS-structure-based 3D printed anti-infection bone scaffold in the preparation of bone repair materials.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The bone scaffold of the present invention is a G-unit structure of TPMS, which has good bionic properties and a large specific surface area. The 3D printing technology used also provides conditions for customizing the internal and external scaffold structures. The dual antibiotic PLGA microspheres and BMP-2 are loaded into the G-unit TPMS scaffold and fixed with hydrogel to form an anti-infective bone scaffold. The BMP-2 and PLGA microspheres in the inner layer form a slow-release spatiotemporal regulation effect in time and space to regulate the growth of osteoblasts and osteoclasts. In vitro experiments also show that the anti-infective bone scaffold has stronger antibacterial ability in the early stage and still maintains a certain antibacterial ability in the later stage. It is proved that the Mox / Fif plga+BMP-2 scaffold has good anti-infection and bone formation-promoting abilities, providing a new material and idea for the treatment of infected bone defects.
[0025] The biological characteristics, antibacterial properties, in vitro cell compatibility and osteogenic induction effects of the scaffold were studied in vitro. The experimental results showed that the composite scaffold has good sustained antibacterial properties, can significantly promote cell adhesion, has minimal cytotoxicity, has a good effect on promoting cell proliferation, has a significant effect on the early and middle osteogenic differentiation ability of cells, has a significant effect on the late osteogenic differentiation (mineralization and maturation) ability of cells, has a significant effect on the osteogenic ability of cells, has a significant effect on antibacterial properties and antibacterial effects. It is confirmed that the composite scaffold not only has a good osteogenic effect, but also has good antibacterial properties, and can effectively treat infected bone defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a structural schematic diagram and electron microscope scanning diagram of the bone scaffold of the present invention;
[0027] Figure 2 is a basic morphological diagram of different stents in the experimental examples of the present invention;
[0028] Figure 3 is a diagram showing the in vitro release test results of different stents in the experimental examples of the present invention;
[0029] Figure 4 is a diagram showing the effects of different scaffolds on cell adhesion in the experimental examples of the present invention;
[0030] Figure 5 is a graph showing the effects of different scaffolds on cell viability in the experimental examples of the present invention;
[0031] Figure 6 is a graph showing the effects of different scaffolds on cell toxicity and proliferation in the experimental examples of the present invention;
[0032] Figure 7 It is an alkaline phosphatase (ALP) staining effect diagram in the experimental example of the present invention;
[0033] Figure 8is the quantitative result of alkaline phosphatase (ALP) of different scaffolds in the experimental examples of the present invention;
[0034] Fig. 9 This is a diagram showing the effect of alizarin red dyeing in an experimental example of the present invention;
[0035] Fig.10 is the quantitative result of calcium nodules of different stents in the experimental examples of the present invention;
[0036] Fig.11 This is a graph showing the expression of osteogenic proteins Runx2, OPN and OST on each group of scaffolds detected by Western-blot in the experimental example of the present invention;
[0037] Fig.12 is the bacterial concentration in the plate count medium of the co-culture of different scaffolds and bacteria in the experimental examples of the present invention;
[0038] Fig.13 It is the quantitative result of plate count of co-culture of different scaffolds and bacteria in the experimental examples of the present invention;
[0039] Fig.14 are the antibacterial ring results of different stents in the experimental examples of the present invention;
[0040] Fig.15 is the crystal violet staining result of bacterial biofilms of different scaffolds in the experimental examples of the present invention;
[0041] Fig.16 is the quantitative result of crystal violet staining of bacterial biofilms of different scaffolds in the experimental examples of the present invention;
[0042] Fig.17 These are the live bacteria / dead bacteria staining results of different stents in the experimental examples of the present invention. DETAILED DESCRIPTION
[0043] The embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and examples.
[0044] Embodiment 1:
[0045] The present invention provides a 3D printed bone scaffold based on the TPMS structure. The bone scaffold is prepared by 3D printing using Ti-6Al-4V powder as a building material. The bone scaffold is a G unit structure of TPMS. The porosity increases radially from the inner layer to the outer layer. The pore size range is 420-630 μm, the inner layer porosity is 55%, the peripheral porosity is 90%, the scaffold diameter is 15 mm, and the height is 2 mm. The bone scaffold has excellent performance and can be used to carry drugs to form a new material for treating infected bone defects. Through the sustained release of drugs, the two key points of early thorough debridement and high-concentration antibiotic treatment and later guidance of rapid bone regeneration can be grasped.
[0046] As attached Figure 1 As shown, it can be seen from the electron microscope scanning that the bone scaffold has good bionic properties and a large specific surface area.
[0047] The bone scaffold was prepared using 3D printing technology, with Ti-6Al-4V powder as the building material, and prepared by selective laser melting (SLM); the sample was constructed layer by layer with a 30μm laser spot;
[0048] The printing laser power was 100 W, the hatch spacing was 70 μm, the laser scanning speed was 400 mm / s, the build plate temperature was 35 °C, and the alternating hatch mode was used as the scanning strategy;
[0049] The samples were built layer by layer with a thickness of 50 μm. The 3D printing process was carried out in an argon atmosphere. After the SLM process, the samples were cleaned and cooled to room temperature.
[0050] Embodiment 2:
[0051] The present invention is based on the 3D printed bone scaffold based on the TPMS structure provided in Example 1, loaded with two antibiotics and bone morphogenetic protein-2, to form a 3D printed anti-infection bone scaffold based on the TPMS structure, the bone scaffold is prepared by 3D printing with Ti-6Al-4V powder as the building material, the bone scaffold is the G unit structure of TPMS, the porosity increases radially from the inner layer to the outer layer, the pore size range is 420-630 μm, the inner layer porosity is 55%, the peripheral porosity is 90%, the scaffold diameter is 15 mm, the height is 2 mm, the bone scaffold is loaded with moxifloxacin / rifampicin polylactic acid-glycolic acid microspheres (PLGA microspheres) and bone morphogenetic protein-2 (BMP-2), and fixed with hydrogel. By loading PLGA microspheres and BMP-2, a spatiotemporal slow-release sequential regulation structure is formed. The prepared bone scaffold has a stronger antibacterial ability in the early stage, and mainly promotes osteogenesis in the later stage, but still maintains a certain antibacterial ability to regulate the growth of osteoblasts and osteoclasts.
[0052] Embodiment 3:
[0053] This example provides a specific preparation method of the 3D printed anti-infection bone scaffold based on the TPMS structure provided in Example 2. The 3D printed bone scaffold based on the TPMS structure prepared in Example 1 is used to prepare moxifloxacin / rifampicin PLGA microspheres, referred to as PLGA dual antibiotic microspheres, during loading.
[0054] PLGA double antibiotic microspheres were prepared by double emulsion-solvent evaporation method, with oil phase as the external phase and water phase as the internal phase.
[0055] The preparation method of the external phase liquid is as follows: 25 ml of liquid paraffin and petroleum ether and 10 mg of moxifloxacin are taken in a 100 ml beaker, and a stirrer is added to run on a stirrer for 1 hour (stirring speed is 50 r / min) to make it fully saturated, and then the mixed solution is divided into 15 ml centrifuge tubes, and after centrifugation at (4000 r / min) for 15 minutes, the supernatant is taken and put into a 100 ml beaker. 0.1% Span85 (0.049 g) is dropped into 50 ml of the supernatant, and stirred again for 50 minutes.
[0056] The preparation method of the internal phase liquid is as follows: take 150ul acetonitrile and 750ul isopropanol in a 2ml EP tube, weigh 80mg PLGA (50 / 50, molecular weight 10,000) and dissolve it in the above solution, vortex for 5min, ultrasonic for 1h, add 10mg moxifloxacin and 10mg rifampicin to the ultrasonically dissolved 80mg PLGA internal phase liquid, vortex for 10min, then add 100ul dichloromethane, and vortex again for 5min to fully dissolve it.
[0057] The external phase liquid and the internal phase liquid are prepared. 20ml of the external phase liquid is taken into a 50mL beaker for shearing. 1ml of the internal phase liquid is poured into the 20ml external phase liquid and sheared at (8000r / min) for 30s on a high-speed disperser. Then the remaining 30ml of the external phase liquid is poured into the mixed liquid and placed on a vortex machine for vortexing for 4h (stirring speed is 50r / min). As the vortexing process proceeds, petroleum ether evaporates, and small pink particles of microspheres can be seen in the solution. The solution is poured into a 15ml centrifuge tube and centrifuged for 15min, the supernatant is discarded, 5ml of detergent (petroleum ether and n-hexane are configured in a 1:1 ratio), vortexed for 2min, centrifuged for 2min, and the above cleaning method is repeated 3 times. After discarding the supernatant, only the microspheres are left. The microspheres are placed on a culture dish and fully dried for 48h.
[0058] The hydrogel preparation process is as follows:
[0059] Prepare 0.25% (w / v) initiator standard solution
[0060] (1) Take 20 ml of PBS and add it to a brown bottle containing initiator LAP (containing 0.05 g LAP);
[0061] (2) Heat the solution in a 40-50°C water bath for 15 minutes, shaking several times during the process;
[0062] The LAP standard solution can be stored at 4°C in the dark for 12 months.
[0063] Prepare GelMA solution (recommended GelMA concentration is 5-30% (w / v))
[0064] (1) Take the required amount of GelMA and place it in a light-proof centrifuge tube;
[0065] (2) Add the initiator standard solution to the above centrifuge tube and shake to fully soak the GelMA;
[0066] (3) Heat in a water bath at 60-70°C in the dark for 20-30 minutes, shaking several times;
[0067] (4) The GelMA solution was immediately sterilized using a 0.22 μm sterile pillow filter (to prevent low-temperature gelation).
[0068] Preparation of anti-infective bone scaffold: The 3D printed bone scaffold (titanium scaffold) prepared in Example 1 was used. This scaffold has good biomimetic properties and a large specific surface area. The titanium scaffold was ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water for 15 minutes in sequence, sterilized by high-pressure steam sterilization, and then dried for use. The sterilized and dried scaffold was placed in a suitable flat-bottomed container, and the prepared moxifloxacin / rifampicin PLGA microspheres were fully mixed with 0.5 ml of hydrogel, poured into the flat-bottomed container, and the hydrogel was fully wrapped with the scaffold, vortexed on a vortex oscillator, and irradiated with a 405nm ultraviolet flashlight to photocured the hydrogel. After waiting for 24 hours, 20ul BMP-2 solution (containing 5% trehalose carrier protein) was dissolved in 0.5ml hydrogel, and then the 0.5ml BMP-2-containing hydrogel was poured into the semi-processed scaffold made on the first day, vortexed on a vortex oscillator, and irradiated with a 405nm ultraviolet flashlight to photocured the hydrogel to obtain a 3D printed anti-infection bone scaffold based on the TPMS structure.
[0069] Embodiment 4:
[0070] The present invention provides the use of the 3D printed anti-infection bone scaffold based on the TPMS structure in Example 2 and the 3D printed anti-infection bone scaffold based on the TPMS structure prepared by the preparation method in Example 3 in the preparation of bone repair materials.
[0071] Embodiment 5:
[0072] The present invention adopts a specific experiment to analyze the application effect of the 3D printed anti-infection bone scaffold based on the TPMS structure in Example 2 (that is, the 3D printed anti-infection bone scaffold based on the TPMS structure prepared by the method described in Example 3):
[0073] 1. Experimental Grouping
[0074] The basic morphologies of the four different bracket groups are shown in Figure 2 ,in:
[0075] ①Mox / Fif plga+BMP-2scaffold Group: This group consists of PLGA microspheres containing moxifloxacin (Mox) and rifampicin (Fif), and bone morphogenetic protein-2 (BMP-2) is also added. This combination is designed to evaluate the combined release of antibiotics moxifloxacin and rifampicin with growth factor BMP-2 on the effects of promoting bone tissue formation and anti-infection. BMP-2 can promote osteoblast differentiation and bone formation, while antibiotics are used to inhibit infection and ensure the sterility of the regeneration environment.
[0076] ②Mox / Fif plga scaffold Group: This group of scaffolds contains moxifloxacin and rifampicin PLGA microspheres, but does not contain BMP-2. This combination is used to study the effect of antibiotic-loaded PLGA scaffolds on tissue repair in the absence of growth factors.
[0077] ③Mox / Fif Powder scaffold Group: Unlike the first two groups, this group used moxifloxacin and rifampicin in powder form instead of delivery through PLGA carrier. This group was established to evaluate the basic effect of direct use of drug powder on tissue regeneration and compare it with delivery through polymer scaffolds.
[0078] ④Blank scaffold Group: This is a control group using a blank scaffold without any drugs or growth factors. This group is used to evaluate the effect of the PLGA scaffold itself on tissue response and regeneration.
[0079] 2. In vitro release experiment
[0080] The results of in vitro release experiments are shown in Figure 3 , Result interpretation: The release effects of antibiotics in the Mox / Fif plga+BMP-2scaffold Group and the Mox / Fif plga scaffold group were similar in the early, middle and late stages, and both achieved antibacterial effects. Although the Mox / Fif powder scaffold group had a higher release rate in the early stage, the release rate in the middle and late stages did not achieve the antibacterial effect, which confirmed that the sustained antibacterial performance of plga-form antibiotics was better, and confirmed that the sustained antibacterial performance of the composite scaffold was good.
[0081] 3. In vitro biological performance evaluation
[0082] 1. Observe the effect of each group of scaffolds on cell adhesion
[0083] Specific operation: Place each group of sterilized composite scaffolds in a 6-well plate, add a certain amount of complete culture medium to each well to immerse the scaffold, aspirate the culture medium after 24 hours and start inoculating cells. 5 / mL of cell suspension was inoculated on the surface of the material, and then 2900μl of culture medium was added to cover the entire scaffold. The culture plate inoculated with cells was placed in a cell culture incubator. After 24 hours of co-culture, the culture medium was aspirated, rinsed with PBS buffer 3 times, and then 4% paraformaldehyde solution was added to immerse the scaffold at room temperature for 10 minutes, the paraformaldehyde solution was aspirated, and then rinsed with PBS containing 0.1% TritonX-100 3 times, each time for 5 minutes. Actin-Tracker Green was diluted with PBS containing 5% bovine serum albumin (BSA) and 0.1% TritonX-100 at a ratio of 1:100 to obtain the staining working solution. An appropriate amount of staining working solution was added to each well to immerse the scaffold, incubated at room temperature in the dark for 30 minutes, and rinsed with PBS buffer containing 0.1% TritonX-100 3 times, each time for 5 minutes. Then 2.5ml of DAPI staining solution with a concentration of 1ug / mL was added to each well and incubated in the dark for 5 minutes, aspirated and rinsed with PBS buffer 3 times, each time for 5 minutes. After staining, the scaffold was placed on a fluorescence microscope to observe the cytoskeleton morphology on the scaffold surface. Figure 4 , Result interpretation: Cell morphology was observed by FITC-phalloidine / DAPI staining. Under the microscope, the cytoplasm of each group of cells was clear, the nucleus was full, the cell morphology of each group was mature, and the microfilaments were interwoven into a mesh structure. The number of microfilament skeletons in the Mox / Fif plga+BMP-2scaffoldgroup was significantly higher than that in the blank group, indicating that the composite scaffold can significantly promote cell adhesion.
[0084] 2. Observe the effect of each group of scaffolds on cell viability
[0085] Specific operation: Place each group of sterilized composite scaffolds in a 6-well plate, add a certain amount of complete culture medium to each well to immerse the scaffold, aspirate the culture medium after 24 hours and start inoculating cells. 5 / mL of cell suspension was inoculated on the surface of the material, and then 2900μl of culture medium was added to cover the entire scaffold. The culture plate inoculated with cells was placed in a cell culture incubator. The medium was changed every 2 days, and live / dead cell staining was performed on the 1st and 3rd day of co-culture.
[0086] ① Dilute 10×Assay Buffer 10 times with deionized water to prepare 1×Assay Buffer working solution;
[0087] ② Prepare Calcein-AM (2mM) and PI (1.5mM) stock solutions and return them to room temperature. Take 5μL of Calcein-AM solution and 15μL of PI solution and add them to 5mL of 1×Assay Buffer working solution for cell staining. Since Calcein-AM is easily hydrolyzed and has poor stability, the staining working solution must be prepared and used immediately and should be used up within the same day;
[0088] ③ Aspirate the culture medium in the well plate and rinse with 1×Assay Buffer 3 times;
[0089] ④ Add an appropriate amount of staining working solution to immerse the material, and incubate at room temperature away from light for 30 minutes;
[0090] ⑤Observe the labeled cells under a fluorescence microscope.
[0091] See Figure 5 , Result interpretation: Green / red fluorescence of osteoblasts on each group of scaffolds after Calcein-AM and PI staining.
[0092] It can be seen that the cells adhered well to the scaffolds in each group. The cell density increased significantly after 3 days of co-culture, and no obvious dead cells were observed in each group, indicating that the cell viability increased from the 1st day to the 3rd day. The cell density of the Mox / Fif plga+BMP-2scaffold group was the largest, indicating that the composite scaffold had the least cytotoxicity.
[0093] 3. Observe the effects of each group of scaffolds on cell toxicity and proliferation
[0094] Specific operation: Each group of sterilized composite scaffolds was placed in a 6-well plate, with 3 replicates in each group. A certain amount of complete culture medium was added to each well to immerse the scaffold. After 24 hours, the culture medium was discarded and cells were inoculated. 100 μL of cell suspension with a concentration of 1×105 / mL was inoculated on the surface of the material, and then 2900 μL of culture medium was added to cover the entire scaffold. The culture plate inoculated with cells was placed in a cell culture incubator, and the medium was changed every 2 days. At the time points of the 1st, 3rd, 5th, and 7th days of co-culture, the CCK-8 reagent and culture medium were diluted 1:10. After discarding the culture medium in each well, 3 mL of the diluted CCK-8 reagent was added (be careful not to generate bubbles in the well), and the culture plate was placed in the incubator for incubation for 4 hours. The supernatant of each well was collected and transferred to a 96-well plate. The absorbance (OD value) at a wavelength of 450 nm was measured using an enzyme marker.
[0095] Result interpretation: Cell CCK-8 test results are as follows Figure 6As shown, after the cells were co-cultured with each group of scaffolds for 1, 3, 5, and 7 days, the number of cells continued to increase, and the OD value of the Mox / Fif plga+BMP-2scaffold group was significantly different from the P value of the blank group (P < 0.05), confirming that the Mox / Fif plga+BMP-2scaffold group has a good effect in promoting cell proliferation.
[0096] 4. Effect of Scaffold on Osteogenic Differentiation of Cells
[0097] 1. Alkaline phosphatase (ALP) staining
[0098] Specific operation: Use a 6-well Transwell plate with a pore size of 8.0 μm, place the composite scaffold in the lower chamber, and inoculate 100 μL of 1×10 5 / mL cells, and the same number of cells were inoculated in the upper chamber of the blank well as a blank control group, with 3 replicates in each group. Then continue to add 2900μL of culture medium to cover the upper and lower chambers of the Transwell plate. After 24 hours of co-culture, the complete culture medium was replaced with osteogenic induction medium (10nM dexamethasone + 50μg / mL ascorbic acid + 10mMβ-glycerophosphate + α-MEM culture medium), placed in a cell culture incubator, and the medium was changed every 3 days. At the 7th and 12th day of co-culture, the culture medium was aspirated, rinsed 3 times with PBS buffer, and then the upper chamber was immersed in 4% paraformaldehyde solution for 10 minutes, and the paraformaldehyde solution was aspirated and discarded.
[0099] Result interpretation: After 7 and 12 days of osteogenic induction, the quantitative detection results of ALP in each group were as follows Figure 7 and 8 As shown in the figure, the quantitative detection results of ALP at two time points indicated that the amount of ALP in the Mox / Fif plga+BMP-2scaffold group was significantly different from that in the blank scaffold group (P<0.05), indicating that the composite scaffold has a significant promoting effect on the early and middle osteogenic differentiation ability of cells.
[0100] 2. Alizarin Red Staining
[0101] Specific operation: Use a 6-well Transwell plate with a pore size of 8.0 μm, place the composite scaffold in the lower chamber, and inoculate 100 μL of 1×10 5 / mL cells, and the same number of cells were inoculated in the upper chamber of the blank well as a blank control group, with 3 replicates in each group. Then continue to add 2900μL of culture medium to cover the upper and lower chambers of the Transwell plate. After 24 hours of co-culture, the complete culture medium was replaced with osteogenic induction medium (10nM dexamethasone + 50μg / mL ascorbic acid + 10mMβ-glycerophosphate + α-MEM culture medium), placed in a cell culture incubator, and the medium was changed every 3 days. At the 7th and 12th day of co-culture, the culture medium was aspirated, rinsed with PBS buffer 3 times, and then the upper chamber was immersed in 4% paraformaldehyde solution for 10min. After the paraformaldehyde solution was aspirated, an appropriate amount of Alizarin Red staining working solution was added to each well, and the staining was performed at room temperature for 30min, the staining solution was aspirated, and it was rinsed with deionized water to remove non-specific precipitation. The membrane was carefully peeled off with tweezers, the bottom surface was facing up to dry, and it was moved to a slide and placed under a microscope to observe the staining. After the observation, the membrane was placed in a clean vessel, and then 10% cetylpyridinium chloride solution was added to each well to dissolve the Alizarin Red precipitate. After it was completely dissolved, it was transferred to a 96-well plate and the OD value at a wavelength of 620 nm was measured using an enzyme reader.
[0102] Result interpretation: After 21 and 28 days of osteogenic induction, the quantitative detection results of calcium nodules in each group were as follows Fig. 9 and 10 As shown in the figure, the quantitative detection results of calcium nodules at two time points indicated that the amount of ALP in the Mox / Fif plga+BMP-2scaffold group was significantly different from that in the blank scaffold group (P<0.05), indicating that the composite scaffold has a significant promoting effect on the late osteogenic differentiation (mineralization maturation) of cells.
[0103] 3. Western-blot detection of osteogenesis-related markers
[0104] Specific operation: Use a 6-well Transwell plate with a pore size of 8.0 μm, place the composite scaffold in the lower chamber, and inoculate 100 μL of 1×10 5 / mL cells, and the same number of cells were inoculated in the upper chamber of the blank well as a blank control group, with 3 replicates in each group. Then 2900μL of culture medium was added to cover the upper and lower chambers of the Transwell plate. After 24 hours of co-culture, the complete culture medium was replaced with osteogenic induction medium (10nM dexamethasone + 50μg / mL ascorbic acid + 10mM β-glycerophosphate + α-MEM culture medium), placed in a cell culture incubator, and the medium was changed every 3 days.
[0105] On the 21st day of co-culture, the culture medium was aspirated, and the cells were rinsed with PBS buffer three times. The PBS was aspirated, and the cells on the upper side of the upper chamber membrane were carefully wiped with a wet cotton swab. The membrane was carefully peeled off with small tweezers and moved to a clean vessel with the bottom side facing up. Proteins were extracted and Western-blotted to detect osteogenic markers (Runx2, OST, OPN proteins). The operation steps are as follows:
[0106] (1) Protein extraction
[0107] ① Add an appropriate amount of RIPA lysis buffer (100:1) containing protease to the vessel containing the upper chamber membrane, and use a pipette to blow with appropriate force to make the lysis buffer fully contact with the cells on the membrane;
[0108] ② Place on ice for lysis for 10 minutes;
[0109] ③ Use a cell scraper to scrape the cells off the membrane and transfer the scraped mixed solution to an EP tube;
[0110] ④ Centrifuge at 12000 rpm for 15 min at 4°C;
[0111] ⑤ Transfer the supernatant to a new 1.5 mL EP tube and store the resulting protein solution in a -20°C refrigerator.
[0112] (2) BCA method for protein concentration determination
[0113] ① Prepare protein standards of different concentrations according to the instructions of the kit, add them to 96-well plates, 20 μL per well, and set up 3 replicate wells for each concentration;
[0114] ② Add 2 μL of protein solution to a 96-well plate, then fill up to 20 μL with PBS and set up 3 replicate wells;
[0115] ③ Add 200 μL of the prepared BCA working solution to each well, mix well and incubate at 37°C for 30 min;
[0116] ④ Use an enzyme marker to measure the OD value at a wavelength of 560nm, draw a standard curve with the standard content as the horizontal axis and the OD value as the vertical axis, and calculate the concentration of the protein to be tested.
[0117] (3) Western-blot
[0118] ① Glue preparation: After cleaning and drying, fix the glass plate on the glue pouring plate, add the rapid accelerator and shake the glue well, prepare 10% separation gel and 5% concentration gel, and pull out the electrophoresis comb after solidification;
[0119] ② Sample preparation: Take 120 μL of the protein supernatant to be tested and mix with 30 μL of 5× loading buffer, boil in boiling water for 5 minutes and then let it cool;
[0120] ③ Electrophoresis: Add 2μL of Maker to each comb hole and 10μL of protein sample. Electrophoresis is performed at a constant voltage of 75V for 130min until the Marker reaches the bottom;
[0121] ④ Transfer: Immerse the gel completely in the transfer solution, use a constant current of 300mA, and transfer it to the PVDF membrane by utilizing the charge-carrying property of the protein;
[0122] ⑤ Blocking: Block the PVDF membrane with 5% BSA at room temperature for 90 minutes;
[0123] ⑥ Primary antibody incubation: Incubate with primary antibody diluted in 1×PBST at room temperature for 60 minutes, shake slowly on a shaker at 4°C overnight, and then stand at room temperature for 30 minutes: RunX-2 (titer: 1:1000), OPN (titer: 1:1000), OST (titer: 1:1000), β-actin (titer: 1:5000). Then wash the membrane 3 times with 1×PBST on a shaker, 10 minutes each time;
[0124] ⑦ Secondary antibody incubation: Incubate with secondary antibody diluted in 1×PBST at room temperature for 80 min: HRP goat anti-rabbit IgG (titer: 1:6000); then wash the membrane 3 times with 1×PBST on a shaker, each wash for 15 min;
[0125] ⑧ Color development / exposure: Mix the A / B solution in the ECL chemiluminescence kit in a 1:1 volume ratio. Immerse the PVDF membrane in the prepared working solution for 2 minutes, absorb the excess liquid, then wrap the PVDF membrane with plastic wrap and remove bubbles. Use a gel imaging system to observe the bands and develop and rinse;
[0126] ⑨Analysis: Scan the film and use quantity one software for protein quantitative analysis.
[0127] Result interpretation: Western-blot was used to detect the expression of osteogenic proteins Runx2, OPN, and OST on the scaffolds of each group. Fig.11 As shown, the expression of osteogenic proteins in the Mox / Fif plga+BMP-2scaffold group was significantly different from that in the blank scaffold group (P<0.05), indicating that the composite scaffold has a significant promoting effect on the osteogenic ability of cells.
[0128] 5. Antibacterial properties
[0129] 1. Count results of each group of stent plates
[0130] Specific operation: Use a sterile cotton swab to gently pick up 3-4 colonies on the TSA agar plate, add sterile PBS buffer to wash the bacteria, then take out 3mL of liquid and place it in a turbidimetric tube to measure its turbidity, and then dilute the bacteria according to the experimental requirements. Place each group of sterilized brackets in a 6-well plate, and then add 3mL of 1.0×10 6 CFU / mL diluted bacterial solution, set up 3 replicates for each group. Place the well plate in a constant temperature incubator at 37°C for co-culture. After 24 hours, remove the bracket, wash the free bacteria with PBS buffer, and then put it into a centrifuge tube containing PBS buffer. After ultrasonic cleaning for 10 minutes, dilute the eluate 10 times and 100 times respectively, and then take 100μL of the diluted bacterial solution and evenly apply it on the TSA plate. After incubation for 24 hours, use image J software to count the plates and calculate the inhibition rate.
[0131] Result interpretation: After 24 hours of co-culture of the scaffolds with bacteria, the number of bacteria adhering to each scaffold was counted by plate counting method. Fig.12 and 13 As shown, there was a significant difference between the Mox / Fif plga+BMP-2scaffold group and the blank scaffold group (P < 0.001), confirming that the composite scaffold has significant antibacterial properties.
[0132] 2. Antibacterial rings of each group of stents
[0133] Specific operation: Take 100 μL of the concentration of 1.0×10 7 CFU / mL bacterial solution, evenly spread on the TSA plate with a coating rod. Place each group of brackets in the center of the plate, and do not place any brackets in the blank group. Set up 3 samples in each group. Incubate in a constant temperature incubator at 37℃ for 24 hours and then take out for observation. The larger the area around the microspheres without bacterial growth, the better the antibacterial ability.
[0134] Interpretation of results: Fig.14 As shown, after measurement, all four groups of scaffolds have antibacterial properties, but the Mox / Fif plga+BMP-2scaffold group has the best antibacterial property.
[0135] 3. Bacterial biofilm staining of each group of scaffolds
[0136] Specific operation: A 6-well Transwell plate with a pore size of 8.0 μm was selected, and the composite scaffold was placed in the upper chamber of each well, and then 1.0×10 6CFU / mL, and the same number of bacteria was inoculated in the lower chamber of the blank well as a blank control group, with 3 replicates in each group. After 24 hours, the upper chamber was removed and the lower chamber was gently washed with PBS buffer to prevent the biofilm from being washed off. Fix with 4% paraformaldehyde solution for 20 minutes and dry for 12 hours, then add 0.5% crystal violet solution and stain at room temperature for 10 minutes. Wash with PBS buffer 3 times to remove excess staining solution, and observe under a microscope after drying. Dissolve the biofilm with 33% acetic acid solution, and measure the OD value at a wavelength of 575nm with an enzyme marker.
[0137] Interpretation of results: Fig.15 and 16 After each group of scaffolds and bacteria were co-cultured in LB medium for 1 day, biofilms were generated. The Mox / Fifplga+BMP-2scaffold group showed significant differences compared with the blank scaffold group (P<0.001), confirming that the scaffold has good antibacterial properties.
[0138] 4. Live / Dead Bacteria Staining
[0139] Specific operation: Place each group of sterilized scaffolds into a 6-well plate, and then add 3 mL of 1.0×10 6 CFU / mL diluted bacterial solution, set up 3 replicates for each group. Place the well plate in a constant temperature incubator at 37°C for co-culture. After 24 hours, add SYTO 9 / PI dye diluted 10 times with PBS buffer and incubate at room temperature in the dark for 10 minutes, then observe under a fluorescence microscope.
[0140] Interpretation of results: Fig.17 As shown, green fluorescence indicates live S. aureus, and red fluorescence indicates dead S. aureus. The dead bacteria in the Mox / Fif plga+BMP-2scaffold group were significantly different from those in the blank scaffold group, confirming that the scaffold had a significant antibacterial effect.
[0141] The biological characteristics, antibacterial properties, in vitro cell compatibility and osteogenic induction effects of the scaffold were studied in vitro. The experimental results showed that the composite scaffold has good sustained antibacterial properties, can significantly promote cell adhesion, has minimal cytotoxicity, has a good effect on promoting cell proliferation, has a significant effect on the early and middle osteogenic differentiation ability of cells, has a significant effect on the late osteogenic differentiation (mineralization and maturation) ability of cells, has a significant effect on the osteogenic ability of cells, has a significant effect on antibacterial properties and antibacterial effects. It provides a new material and idea for the treatment of infected bone defects.
[0142] The above are only specific embodiments of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.
Claims
1. A 3D printed bone scaffold based on TPMS structure, characterized by: The bone scaffold is made of Ti-6Al-4V powder as a building material and is prepared by 3D printing. The bone scaffold is a G unit structure of TPMS, and the porosity increases radially from the inner layer to the outer layer. The pore size range is 420-630 μm, the inner layer porosity is 55%, the peripheral porosity is 90%, the scaffold diameter is 15 mm, and the height is 2 mm.
2. A method for preparing a 3D printed bone scaffold based on a TPMS structure, characterized in that: Using 3D printing technology, Ti-6Al-4V powder was used as the building material and prepared by selective laser melting (SLM); The sample was constructed layer by layer with a 30 μm laser spot; The printing laser power was 100 W, the hatch spacing was 70 μm, the laser scanning speed was 400 mm / s, the build plate temperature was 35 °C, and the alternating hatch mode was adopted as the scanning strategy.
3. The method for preparing a 3D printed bone scaffold based on a TPMS structure according to claim 2, characterized in that: When constructing the sample layer by layer, each layer has a thickness of 50 μm; The 3D printing process is carried out in an argon atmosphere; After the SLM process, the samples were cleaned and cooled to room temperature.
4. The 3D printed bone scaffold based on the TPMS structure prepared by the method for preparing the 3D printed bone scaffold based on the TPMS structure according to any one of claims 2 to 3, characterized in that: The bone scaffold is a G unit structure of TPMS, with porosity increasing radially from the inner layer to the outer layer, a pore size range of 420-630 μm, an inner layer porosity of 55%, a peripheral porosity of 90%, a scaffold diameter of 15 mm, and a height of 2 mm.
5. 3D printed anti-infection bone scaffold based on TPMS structure, characterized by: The 3D printed bone scaffold based on the TPMS structure as described in claim 1 or 4 is used, and moxifloxacin / rifampicin PLGA microspheres and BMP-2 are loaded inside the bone scaffold and fixed with hydrogel.
6. The 3D printed anti-infection bone scaffold based on the TPMS structure as claimed in claim 5, characterized in that: During loading, moxifloxacin / rifampicin PLGA microspheres are first prepared by a double emulsion-solvent evaporation method, wherein the external phase liquid is an oil phase and the internal phase liquid is an aqueous phase; the external phase liquid is prepared as follows: liquid paraffin, petroleum ether and moxifloxacin are placed in a beaker, stirred to fully saturate them, then centrifuged to obtain a supernatant, 0.1% Span85 is dropped into the supernatant and stirred again, wherein the liquid paraffin: petroleum ether: moxifloxacin = 5ml: 5ml: 2mg; the internal phase liquid is prepared as follows: an appropriate amount of PLGA is dissolved in an acetonitrile and isopropanol solution, vortexed, ultrasonicated, then moxifloxacin and rifampicin are added, dichloromethane is added after continued vortexing, and vortexed again to fully dissolve them, wherein the acetonitrile: isopropanol: PLGA: moxifloxacin: rifampicin: dichloromethane = 15ul: 75ul: 8mg: 1mg: 1mg: 10ul.
7. The 3D printed anti-infection bone scaffold based on the TPMS structure as claimed in claim 6, characterized in that: After the external phase liquid and the internal phase liquid are prepared, first take an appropriate amount of the external phase liquid in a beaker for shearing and set aside, add the internal phase liquid to the external phase liquid, shear on a high-speed disperser, then add the external phase liquid, place it on a vortex machine and vortex it. As the vortexing proceeds, pink small particle microspheres are seen in the solution, then centrifuge and discard the supernatant, add detergent and vortex centrifuge to obtain microspheres, and fully dry them on a culture dish to obtain moxifloxacin / rifampicin PLGA microspheres; the external phase liquid added first: the internal phase liquid: the external phase liquid added later = 20ml: 1ml: 30ml, and the washing liquid is prepared by petroleum ether and n-hexane in a ratio of 1:
1.
8. The 3D printed anti-infection bone scaffold based on the TPMS structure as claimed in claim 7, characterized in that: The bone scaffold is ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water in sequence, sterilized by high-pressure steam sterilization, and then dried for use; the sterilized and dried scaffold is placed in a suitable flat-bottomed container, and the prepared moxifloxacin / rifampicin PLGA microspheres are fully mixed with the hydrogel, poured into the flat-bottomed container, so that the hydrogel fully wraps the scaffold, vortexed on a vortex oscillator, and irradiated with a 405nm ultraviolet flashlight to photocured the hydrogel to obtain a semi-processed scaffold; After waiting for 24 hours, the BMP-2 solution was dissolved in the hydrogel, and then the BMP-2-containing hydrogel was poured into the semi-processed scaffold made on the first day, vortexed on a vortex oscillator, and irradiated with a 405nm ultraviolet flashlight to photocured the hydrogel to obtain a 3D printed anti-infection bone scaffold based on the TPMS structure.
9. Use of the 3D printed bone scaffold according to claim 1 and / or the 3D printed bone scaffold according to claim 4 and / or the 3D printed anti-infective bone scaffold according to any one of claims 5 to 8 in the preparation of bone repair materials.
Citation Information
Patent Citations
Simple method for preparing PLGA microspheres with uniform particle size
CN105232474A
TPMS (Tire Pressure Monitor System) porous bone replacement stent
CN116077723A
Cartilage repair scaffold and preparation method thereof
CN118697942A
Method for preparing Rifampiciu microballs covered by degradable high-molecular material
CN1437933A
Cited By
3D printing metamaterial piezoelectric bone defect repair stent and preparation method thereof
CN120132062A